Prevalence of burnout syndrome in university students: A systematic review - Rosales-Ricardo, Yury (2021)
Background. Burnout syndrome is a social and health problem in college students. Objective. To synthesize evidence from previous studies on the prevalence of burnout syndrome in university students in their three-dimensional approach. Method. The search strategies followed the PRISMA guidelines and were based on the following descriptive terms: “burnout,” “studies,” “prevalence,” “students.” Pubmed, Web of Science Core Collection, PsicINFO, and Scielo were consulted. An evaluation of the quality of the information was carried out applying the STROBE positioning guidelines. Results. We found 1,406 studies that were reduced to 46 studies for final analysis using the STROBE statement, eventually leaving 20 studies. One study (5%) was conducted in North America, five (25%) in Asia, nine (45%) in Latin America, and five (25%) in Europe. Of the 20 studies evaluated in the systematic review, those that had the best overall evaluation in the STROBE analysis were selected for discussion, corresponding to 10 (out of 75% of STROBE). Overall prevalence of each dimension of the syndrome was estimated at 55.4% for emotional exhaustion, 31.6% for cynicism, and 30.9% for academic efficacy. Discussion and conclusion. Moderate levels of burnout syndrome prevail in the different populations of university students of different careers worldwide. In only a few studies is the prevalence low and this could be due to multiple evaluative variables.